Reinforced (un)predictability and the voluntary operant. Issue 1 (2nd January 2016) - Neuringer, Allen
ABSTRACT: The operant is comprised of a class of responses. Each member of the class (or each response instance) has a probability of emergence (or emission). Reinforcers control response types (e.g., topographies) and attributes (e.g., forces, latencies), including the individual probabilities of class members. Control by reinforcers over response types and probabilities implies that responses will be (a) functional (because they produce reinforcers) and (b) more-or-less predictable (depending upon the conditions and contingencies). Control by reinforcers over levels of predictability helps to explain why operant responses are correctly described as voluntary and at the same time provides an alternative to hypothesizing that each operant instance is wholly determined by environmental variables. Operant response emissions are probabilistic and therefore at least somewhat unpredictable.